Development of Parenting Card Media to Promote Positive Parenting among Parents of Young Children - Ira Reski Awalia; ⁠Suardi ⁠Suardi; Kartini Marzuki; Herlina Marzuki; Rusmayadi Rusmayadi (Universitas Islam negeri Mahmud Yunus Batusangkar, 2026)
Positive parenting practices among parents are still relatively low and inconsistent, with a lack of practical tools to support positive parenting. Parenting classes are only offered through workshops, seminars, and other face-to-face sessions. This study aimed to develop a parenting card as an interactive educational media to foster positive parenting among parents of early childhood children. The research employed a Research and Development method using the ADDIE model, which consists of Analysis, Design, Development, Implementation, and Evaluation stages. The research subjects included 7 parents in a limited trial to determine the practicality of the media and 14 parents in the implementation stage to examine its effectiveness. The results showed that the parenting card media was categorized as very valid based on expert validation from material and media experts, with an average score of 3.63. The media was also categorized as very practical, with a practicality percentage of 85.11%, indicating that it was easy to use and beneficial for parents. Furthermore, the effectiveness test showed an increase in pre-test and post-test scores, with a significance value of 0.000 < 0.05 based on the paired sample t-test, indicating a significant difference before and after using the media. Based on these findings, it can be concluded that the developed parenting card media is valid, practical, and effective in fostering positive parenting among parents of early childhood children.